Contemporary Progresses in Ultrasonic Welding of Aluminum Metal Matrix Composites - Selvaraj, Senthil Kumaran; Srinivasan, Kathiravan; Chadha, Utkarsh; Mishra, Rajat; Arpit, Kurane; Apurb, Kumar; Hu, Yuh-Chung (Frontiers in Materials, 2021)
The Aluminum metal matrix with particulate reinforcements is the new future of the coming industrial revolution due to the higher strength and availability. Composite reinforcements such as SiC, TiB2, B4C, and others contribute significantly to the increased strength of the Aluminum metal matrix, which can be an optimal choice, also at a lower cost, in some applications where Aluminum is considered or proven to withstand high temperatures. Ultrasonic welding is the process, where, we get the electrical energy, which converts and amplifies into vibration energy for the welding to occur. The challenge we face today is the thickness limitations in ultrasonic welding. The ultrasonic welding of the Aluminum metal sheet with the reinforcements may affect it, as the addition of particulate reinforcements will increase the strength of the Aluminum matrix. Ultrasonic welding can only support a metal sheet with a thickness of up to 2.5 mm in the case of an Aluminum plain sheet. However, if the strength of the Aluminum metal matrix increases, the next step is to achieve ultrasonic welding with the same thickness of Aluminum matrix and reinforced composites that have greater strength than a standard Aluminum sheet. This review will focus on the parameters and the factors which may help decrease the difficulties of Ultrasonic Welding of Aluminum MMC, alongside reviewing the current technologies and research works.